The moderating role of CSR in board gender diversity and firm financial performance: empirical evidence from an emerging economy - Jiang, L.; Cherian, J.; Sial, M. S.; Wan, P.; Filipe, J.; Mata, M. N.; Chen, X. (Economic Research-Ekonomska Istrazivanja, 2021)
The current study aims to investigate the moderating role of corporate social responsibility (CSR) in board gender diversity and firm financial performance. We used the panel data regression (fixed effect) in our analysis to check the moderating role of CSR in the board gender diversity and the firm financial performance. We collected the data of Chinese listed companies from the Shenzhen and Shanghai stock exchanges from the China stock market and accounting research (CSMAR) database. We used a two-stage least square (TSLS) regression model to control the possible problem of endogeneity. Our results show that higher representation of female directors in the board is positively related to firm financial performance and that CSR has a significantly positive effect when moderating the relation between board gender diversity and firm financial performance. Besides, three control variables (board size, board member average age, and Big4) have a positive impact on the firm performance, having the leverage variable a negative impact on the firm performance. Our findings hold for a set of robustness tests. This study has important implications, namely by enriching the existing literature on CSR and by highlighting the importance of board gender diversity, and emphasizing the importance of the reporting of more CSR activities and its impact on the decision-making process.